PIM's modeling expertise used to support the design of the agricultural investment strategies of Malawi and Rwanda - CGIAR Research Program on Policies, Institutions, and Markets (2018)
PIM research using computable general equilibrium modeling has informed the development of the National Agricultural Investment Plans of Malawi and Rwanda. These strategic documents provide a country-wide framework to coordinate and prioritize investments by government agencies, development partners and other actors in the agricultural sector.